Digital designing with programmable logic devices - Carter, John W. (Prentice Hall, 1997)
The purpose of this book is to use hands-on methodology to present programmable logic devices from a viewpoint which will prepare the reader for application within the digital design industry. The knowledge of, and ability to apply state machines to control situations is vital to the overall education of the digital designer.